Implementasi Pengembangan Pariwisata Di Pantai Gresik Harjo Kelurahan Gresik Harjo Kecamatan Palang Kabupaten Tuban - Siti Sutria; M. Kendry Widiyanto; Anggraeny Puspaningtyas (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Gresik Harjo Beach, which is located in Tuban Regency, East Java Province, namely located on the border of Palang and Tuban Regency, is one of the famous beach tourist attractions and is visited by many tourists. Based on the existing potential and existing opportunities, tourism development needs to be carried out in order to increase economic growth by empowering the community's economy. Researchers are interested in knowing how tourism development is implemented in Tuban Regency, and knowing the right model for developing the tourism potential of Kelapa Beach in improving the welfare of the surrounding community. This research is a qualitative descriptive study, with the research object at POKDARWIS Gresik Harjo village and using triangulation techniques. The results of this research are 1. Implementation of Regional Regulation number 9 of 2012 concerning Tuban Regency Spatial Planning for 2012-2032.